Car parking guidance system / Muhammad Aiman Asraf Roslan & Muhammad Fikri Ikhwan Saifuddin - Roslan, Muhammad Aiman Asraf; Saifuddin, Muhammad Fikri Ikhwan (2015)
The main purpose of this project is to implement the skills and knowledge from our study in course Electrical Engineering. Furthermore, we hope the objective of this project are achievable and give the opportunity for mall management to create a better parking system in the future. The first parts of this project are discussions with the supervisor. Which are handle in every week, to create and form work the circuits. Final Year Project 1 are mainly the embodiment of our real project which are only consist of planning and construct the circuit use for Final Year Project 2. The second parts of this project are about teamwork with partner which is really important to ensure the works are done by the due date. In progress of this project, the works are given out equally.